PENGARUH POSITIVE REINFORCEMENT TERHADAP MOTIVASI BELAJAR PENJASKES DI SMAN 1 MENYUKE - Prayogi, Yandi; G. Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is whether there is influence of positive reinforcement to learners motivation in SMAN 1 Menyuke District Landak. The purpose of this research is to know the influence of positive reinforcement on learning motivation of learners at SMAN 1 Menyuke District Landak. The method used in this research is experiment with pre experimental design. The population in this study were all students of class XI at SMAN 1 Menyuke which amounted to 143 and the sample in this study were students of class XI IPA 2 which amounted to 35 with sampling technique using purposive sampling technique that is sample determination technique with certain consideration, such as from observations and observations that researchers do, the motivation to learn learners in following the lesson and learners are not motivated to follow the subjects penjaskes. Data analysis with computerized system and analysis by using t-test. The results showed pretest value of 0.76> 0.05 and posttest value of 0.103> 0.05. Data analysis obtained ttest value with difference of pretest and posttes value is 26,18 with value p value 0,000 <0,05 then Ho rejected and Ha accepted mean there is influence or improvement from motivation learners learners at SMAN 1 Menyuke after given Positive Reinforcement treatment.Keyword: Positive Reinforcement, Learning Motivation Learners.Â